Treinamento muscular inspiratório na apneia obstrutiva do sono do idoso : ensaio clínico randomizado - Fischer, Marcia Kraide (2018)
In obstructive sleep apnea (OSA), repeated efforts against the occluded airway overloads the inspiratory muscles. Age-related muscle fiber loss makes inspiratory force of older persons a subject of interest. The present study aims to gauge the effect of inspiratory muscle training (IMT) on the apnea-hypopnea index (AHI) of older persons with OSA. Methods: In a randomized trial 34 OSA patients, aged 65 years or older, were randomly allocated to IMT or sham-IMT groups. Subjects underwent 8 weeks of training consisting of 30 maximal inspirations followed by 15 minutes of tidal breathing through a PowerBreathe® device, respectively, loaded or unloaded twice daily. The load was increased every two weeks in the IMT group to keep it at 50-80% of the maximal inspiratory pressure (MIP). All patients repeated the respiratory polygraphy, diaphragm thickness (DT), spirometry, and manovacuometry at 8 weeks. Results: Patients in the IMT group completed the protocol with an average reduction in AHI of 1.6 events per hour (95% confidence interval -4.8 to 1.6). In the sham-IMT group the AHI increased by 3.9 events per hour (95%CI 0.1 to 7.7). Significant group×time interaction was observed in generalized estimating equations (GEE) model for AHI (P=0.023) and for MIP (P<0.001). No significant group×time interaction was observed for maximal expiratory pressure (P=0.069), spirometry (P=0.075) and DT (P=0.176). Conclusion: Although the IMT increased MIP in elderly persons, the reduction in AHI obtained suggests limited clinical usefulness if OSA therapy is intended.